Strategi Pemasaran Modalitas Radiologi MRI dengan Metode Analisis Segmentasi,Target, dan Posisi di RS Harapan Keluarga Mataram - Wirawan, Handi (UI Scholars Hub, 2020)
The increasing number of hospitals in Indonesia, as well as the increasing public demand for quality and affordable health facilities, has made competition in the hospital service industry so tight. In order to compete more effectively, hospitals need to implement marketing strategies. This research is a research in the field of hospital marketing management, especially regarding the analysis of segments, targets, market position and product differentiation of services at the general inpatient unit of RSHK Mataram. This study aims to find out empirical evidence about the effect of Segmentation, Targeting, and Positioning Strategies on the marketing strategy of MRI radiology modalities. RSHK is a hospital that has the most complete radiology technology in Lombok and one of them is MRI. however, the system and investment activities carried out have not run optimally in RSHK. This study is based on a condition where each patient requires an MRI examination for certain indications to establish a diagnosis.